Interplay between light and temperature on growth of Chlorella sorokiniana (Chlorellaceae) cultures under laboratory conditions - Silva Benavides, Ana Margarita (2025)
Introduction: The relationship between light and temperature on the growth of Chlorella sorokiniana (Chlorophyceae) cultures was investigated under laboratory conditions. Objective: The aim of this study was to evaluate the influence of different temperature and light intensities on  growth, productivity, chlorophyll of Chlorella sorokiniana UTEX 1230 in laboratory conditions. Methods: The cultures were exposed to a combination of two light irradiances (100 and 200 μmol photons m−2 s−1) and 5 different temperatures (20 °C, 25 °C, 30 °C, 40 °C, 45 °C). Results: At 100 μmol photons m−2 s−1, the culture growth did not differ significantly within 20 °C and 35 °C range. At this irradiance, the maximum attained biomass dry weight was 3.9 g/l after 9 days of cultivation under continuous light. Cultures grown under 200 μmol photons m−2 s−1,showed much larger differences in their growth. Their final dry weight changed according to the following temperatures, 30 °C (6.19 g/l), 25 °C (5.24 g/l), 35 °C (4.33 g/l), 40 °C (2.50 g/l) 45 °C. Therefore, the optimal temperature for productivity of cultures of Chlorella sorokiniana, strongly changed according to the light intensities at which cultures were exposed. At 100 μmol photons m−2 s−1, a large plateau for optimal growth was observed between 20 °C and 35 °C, while at 200 μmol photons m−2 s−1 a clear optimal temperature for productivity was observed at 30 °C. Conclusions: It was interesting to note that culture grown at 20 °C, performed well under 100 μmol photons m−2 s−1, while when exposed to 200 μmol photons m−2 s−1 they were unable to grow. No growth was achieved at 45 °C. Therefore, 40 °C represented the upper limit to appreciate the growth in Chlorella sorokiniana strain UTEX 1230, while the temperature lower limit  changed with light irradiance.